Labor Risk Prevention and Criminal Law - Oré Sosa, Eduardo (2018)
The huge amount of work accidents in Peru has not produced the implementation of policies aimed at reducing occupational accidents rates. Not only that, there is a certain passivity with informal business and persons who break the law, even when it creates risks to workers’ lives. Criminal Law is the best example, because criminal rules do not apply in fact. We have a symbolic norm; that means a situation that counteracts the preventive effect of Criminal Law. In other words, the legislator has weakened non-criminal instances excluding punishment even for the most serious behaviors in which workers’ lives are endangered. In this context, compliance programs play a big role in labor risk prevention and, therefore, in the reduction of criminal rates.